The Socio-economic gradient of obesity in Ireland – Corrigendum - Madden, David (Economic & Social Studies, 2014)
In a paper published in this journal in 2013 concentration indices for obesity were presented for male and female obesity. Decompositions of the indices were also presented. There was an error in the calculations which led to an overstatement of the concentration indices for obesity for both men and women. The decompositions were qualitatively unaffected. The corrected results are presented here.
Article in press
Keywords: obesity; quantitative methods; Ireland